Observation and properties of the orbitally excited B-s2* meson - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Shchukin, A. A.; et al. (Amer Physical Soc, 2008)
We report the direct observation of the excited L=1 state B-s2* in fully reconstructed decays to B+K-. The mass of the B-s2* meson is measured to be 5839.6 +/- 1.1(stat)+/- 0.7(syst) MeV/c(2), and its production rate relative to the B+ meson is measured to be [1.15 +/- 0.23(stat)+/- 0.13(syst)]%.